An unusual presentation of a secondary extramedullary plasmacytoma - Mahmoud Nujeidat; Yosssi Barshai; Zamir M; Novokhatko Galina; Grisko Olga; Livoff A; Zamir D (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
Plasma cell dyscrasias are a group of entities characterized by neoplastic proliferation of a single clone of plasma cells, typically producing a monoclonal Immunoglobulin [1].